Autoimmune Disease Associated CLEC16A Variants Convey Risk of Parkinson’s Disease in Han Chinese - Fan, Hui-Hui; Cui, Lei; Jiang, Xiao-Xia; Song, Ya-Dan; Liu, Shu-Shu; Wu, Ke-Yun; Dong, Hao-Jia; Mao, Miao; Ovlyakulov, Begench; Wu, Hong-Mei; Zhu, Jian-Hong; Zhang, Xiong (Frontiers in Genetics, 2022)
CLEC16A is a membrane-associated endosomal protein implicated in regulating autophagy and antigen presentation. Its genetic variants are broadly associated with multiple autoimmune diseases. Parkinson’s disease (PD), which undergoes autophagy disruption and neuroinflammation, has been clinically long-time observed in association with autoimmune diseases. In this study, we aimed to understand whether the autoimmune disease associated CLEC16A variants pleiotropically modulate PD risk. Five of such CLEC16A variants, including rs6498169, rs12708716, rs12917716, rs7200786, and rs2903692, were selected and analyzed in a Han Chinese cohort comprising 515 sporadic PD patients and 504 controls. Results showed that rs6498169 and rs7200786 were significantly associated with PD susceptibility (P=0.005 and 0.004, respectively; recessive model, P=0.002 and 0.001, respectively). Rs6498169 was also associated with the PD subtype of postural instability/gait difficulty (P = 0.002). Haplotype analysis showed that the AAG module in order of rs6498169, rs12708716, and rs2903692 was associated with the highest risk for PD (P = 0.0047, OR = 1.42, 95% CI = 1.11-1.82). Functional annotation analyses suggested that rs6498169 was with high probability to affect transcription factor binding and target gene expression. In summary, the current study demonstrates that the autoimmune disease associated CLEC16A variants convey risk of PD in Han Chinese. Our findings suggest a pleiotropic role of CLEC16A and strengthen the link between PD and autoimmune diseases.